Effects of Vitamin-D supplementation in sarcopenic elderly: an integrative review (Research, Society and Development, 2022)
Introduction: Sarcopenia, initially defined as skeletal muscle loss, has gained importance and the study of this entity has shown the complexity involved in its pathophysiology, as well as its interaction with other metabolic pathways, such as vitamin-D. The loss of muscle mass increases in conjunction with advancing age, as the concentration of vitamin-D tends to be lower at advanced ages. The update on the interactions of vitamin-D on muscle function and its benefits on muscle health, especially in sarcopenic elderly people, is important to elucidate possible clinical approaches. Methodology: This is an integrative review, which sought to answer the effects of vitamin-D supplementation in sarcopenic elderly, in the following databases: Virtual Health Library (BVS), National Library of Medicine (PubMed MEDLINE) and Scientific Electronic Library Online (Scielo). Results and Discussion: Vitamin-D hypovitaminosis seems to directly influence the pathophysiology of sarcopenia and muscle function. Its supplementation seems to bring benefits such as increased muscle mass and strength and improvement in postural instability, which may influence the reduction of the risk of falls and mortality in elderly patients. However, a consensus has not yet been established, due to divergences in the variables studied. Conclusion: Evidence seems to converge to the idea that beneficial effects are observed mainly in those patients over 65 years of age and with vitamin-D levels below 30nmol/L, supplementing from 700 - 1000 IU/day.